The Palgrave Handbook of Family Sociology in Europe - Castrén, Anna-Maija; Česnuitytė, Vida; Crespi, Isabella; Gauthier, Jacques-Antoine; Gouveia, Rita; Martin, Claude; Moreno Mínguez, Almudena; Suwada, Katarzyna (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XXIII, 660 p. 29 illus., 7 illus. in color.